2021
DOI: 10.3390/diagnostics11101927
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Concordance of PD-L1 Expression between Biopsies and Cytological Specimens in Non-Small Cell Lung Cancer

Abstract: PD-L1 expression assessed by immunohistochemical staining is used for the selection of immunotherapy in non-small cell lung cancer (NSCLC). Appropriate validation of PD-L1 expression in cytology specimens is important as cytology is often the only diagnostic material in NSCLC. In a previous study comprising two different cohorts of paired biopsies and cytological specimens, we found a fairly good cyto-histological correlation of PD-L1 expression in one, whereas only a moderate correlation was found in the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Compared to peripheral blood, BALF is more proximal or “vicinal” to the tumor cells in the lung, so BALF can provide more direct information on the local immune status in lung tissue 13 . The detection of PD-L1 expression by cells derived from BALF is more consistent with paired tissue biopsies, which in turn is better than pleural effusion cells 25 . A tumor microenvironment analysis based on BALF showed that the expression of CXCL9 in BALF of NSCLC patients who responded to nivolumab is higher than non-responders 26 .…”
Section: Application Of Balf In the Diagnosis And Prognosis Of Lung C...supporting
confidence: 53%
“…Compared to peripheral blood, BALF is more proximal or “vicinal” to the tumor cells in the lung, so BALF can provide more direct information on the local immune status in lung tissue 13 . The detection of PD-L1 expression by cells derived from BALF is more consistent with paired tissue biopsies, which in turn is better than pleural effusion cells 25 . A tumor microenvironment analysis based on BALF showed that the expression of CXCL9 in BALF of NSCLC patients who responded to nivolumab is higher than non-responders 26 .…”
Section: Application Of Balf In the Diagnosis And Prognosis Of Lung C...supporting
confidence: 53%
“…Many factors contribute to cytology–histology disagreement as well as to the heterogeneity in the reported agreement rates. This includes the intra‐tumour heterogeneity of PD‐L1 expression [ 26 ], the number of tumour cells in cytology samples [ 27 ] as well as the discordance due to the applied diagnostic tools in tumour sampling and staining procedures including used antibodies [ 28 ]. Further, the type of cytology specimens might have an impact as cytological cell blocks [ 29 , 30 , 31 ] which demonstrated better agreement with histology specimen than cytology imprints [ 14 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to cytology-histology disagreement as well as to the heterogeneity in the reported agreement rates. This includes the intra-tumour heterogeneity of PD-L1 expression [26], the number of tumour cells in cytology samples [27] as well as the discordance due to the Table 3. Agreement between PD-L1 expression in tumour tissue biopsy (≥ 1 and ≥ 50% of tumour cells) and CTCs (n = 27).…”
Section: Discussionmentioning
confidence: 99%
“…Our study only included cytological samples, many of which were not fixed in formalin or embedded in paraffin, which might explain the differences in results. Similarly, while some studies did not find a statistically significant association between PD-L1 expression and sampling site [49,50], comparable to our results (Table 1), others showed that pleural and nodal metastases were more likely to express PD-L1 than primary tumors [42]. Again, the difference in results could potentially be explained by the latter study using FFPE material which largely came from biopsies or surgical resections, while our study only used cytological material fixed and processed in a variety of ways.…”
mentioning
confidence: 92%